2008
DOI: 10.1002/ajmg.a.32614
|View full text |Cite
|
Sign up to set email alerts
|

Band‐like intracranial calcification with simplified gyration and polymicrogyria: A distinct “pseudo‐TORCH” phenotype

Abstract: The combination of intracranial calcification and polymicrogyria is usually seen in the context of intrauterine infection, most frequently due to cytomegalovirus. Rare familial occurrences have been reported. We describe five patients—two male–female sibling pairs, one pair born to consanguineous parents, and an unrelated female—with a distinct pattern of band‐like intracranial calcification associated with simplified gyration and polymicrogyria. Clinical features include severe post‐natal microcephaly, seizur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 33 publications
(36 reference statements)
6
55
3
Order By: Relevance
“…23,24 Importantly, our neuropathologic evaluation demonstrated that the Zika virus-infected fetal brain shares most of the neuroimaging changes seen in other intrauterine TORCH infections and even in pseudo-TORCH phenotypes. 6,7,8,25,26 It is difficult to make a comparison with the neuropathology of such cases because relatively few autopsies with brain examinations have been performed, 27 not only in cases of Zika virus-associated microcephaly but also in other intrauterine fetal brain infections. 28,29 Some changes, especially those of a malformed cortex, have frequently been described as polymicrogyria on MRI, which should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 Importantly, our neuropathologic evaluation demonstrated that the Zika virus-infected fetal brain shares most of the neuroimaging changes seen in other intrauterine TORCH infections and even in pseudo-TORCH phenotypes. 6,7,8,25,26 It is difficult to make a comparison with the neuropathology of such cases because relatively few autopsies with brain examinations have been performed, 27 not only in cases of Zika virus-associated microcephaly but also in other intrauterine fetal brain infections. 28,29 Some changes, especially those of a malformed cortex, have frequently been described as polymicrogyria on MRI, which should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…6 Some cases with fetal, intracranial, bandlike calcifications, similar to those produced by TORCH agents but without confirmed intrauterine viral infection, have been described under the term pseudo-TORCH. 7,8 The most-frequent microorganisms affecting the fetal brain and causing microcephaly, usually accompanied by calcifications, are cytomegalovirus and Toxoplasma gondii. 6 An outbreak of microcephaly in Brazil, causally associated with the Zika virus epidemic since May 2015, has resulted in this emerging viral infection becoming the leading causative agent of microcephaly in South and Central America 9,10 and a serious threat to pregnant women from other countries who have visited that region.…”
mentioning
confidence: 99%
“…Narrowly-defined pseudo-TORCH syndrome (al-Dabbous et al, 1998;Baraitser et al, 1983;Briggs et al, 2008;Burn et al, 1986;Cohen et al, 2012;Ishitsu et al, 1985;Knoblauch et al, 2003;Kulkarni et al, 2010;Nakamura et al, 2011;Reardon et al, 1994;Vivarelli et al, 2001;Watts et al, 2008;Wieczorek et al 1995), also called Baraitser-Reardon syndrome (Vivarelli et al, 2001), or band-like calcification with simplified gyration and polymicrogyria (BLCPMG; MIM: 251290) (Abdel-Salam & Zaki, 2009;Briggs et al, 2008;O'Driscoll et al, 2010), is associated with microcephaly and intracranial calcifications mimicking congenital toxoplasmosis in the absence of infection. Ocular changes are not reported with pseudo-TORCH syndrome / AGS.…”
Section: Overviewmentioning
confidence: 99%
“…These signs include microcephaly (Aalfs et al, 1995;Abdel-Salam & Zaki, 2009;AbdelSalam et al, 1999;Abdel-Salam et al, 2000;Ahmadi & Bradfield, 2007;Aicardi & Goutières, 1984;al-Dabbous et al, 1998;al-Gazali et al, 1999;Alzial et al, 1980;Angle et al, 1994;Atchaneeyasakul et al, 1998;Baraitser et al, 1983;Bogdan, 1951;Book et al, 1953;Briggs et al, 2008;Burn et al, 1986;Cantú et al, 1977;Casteels et al, 2001;Dale et al, 2000;EventovFriedman et al, 2009;Feingold & Bartoshesky 1992;Fisch et al, 1973;Fryns et al, 1995;Hoyeraal et al, 1970;Hordijk et al, 1996;Hreidarsson et al, 1988;Ishitsu et al, 1985;Jarmas et al, 1981;Kloepfer et al, 1964;Knoblauch et al, 2003;Komai et al, 1955;Kozma et al, 1996;Kulkarni et al, 2010;Leung, 1985;Limwongse et al, 1999;McKusick et al, 1966;Mishra et al, 2002;Nakamura et al, 2011;Nemos et al, 2009;Ostergaard et al, 2012;Pearson et al, 2008;Reardon et al, 1994;…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation